Selling Sacredness: Representation of Sedekah Gunung Ritual in Lencoh Village, Boyolali in New Media - Julianne Indah Rachmawati (Universitas Airlangga, 2018)
Sedekah Gunung Ritual is a selametan ceremony which becomes a tradition of the people in Lencoh village, Selo, Boyolali region. This ritual is done as an expression of gratitude and requests to be kept away from danger especially since the eruption of Mount Merapi. Sacred rituals become a tourist attraction or experience commodification. This process requires media space so that the message, information, and knowledge that is constructed can be accepted by the audience. There are three issues discussed. (1) What is the form of the ritual Sedekah Gunung representation? (2) How is the ritual charity representation function? (3) What is the meaning of ritual charity mountain representation? The method used is interpretative qualitative data analysis with observation and interview data collection methods. Research shows that the form of ritual representation of ritual Sedekah Gunung is presented in various articles, news, and videos in new media spaces. Its function is the promotion of alternative tourism in Selo region especially Lencoh village, inviting tourists, and increasing economy-income from the tourism sector. Its meaning is the construction of knowledge disseminated as an attraction in the context of alternative tourism to attract local and foreign tourists. A shift in ritual values from sacred to commodities.